THE EFFECT OF LEARNING CYCLE MODEL IN WRITING NARRATIVE TEXT - srimaharani tanjung (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Abstract :The purpose of this research to know 1) the application of learning cycle model on students’ writing narrative text , 2) The students’ writing narrative text before and after using learning cycle model, 3) whether there is any significant effect of learning cycle model on students’ writing narrative text. This research used experimental model with the pre-experimental design by using one-group pretest and posttest design. The sample of this research is 22 students of class VIII-U by using purposive sampling. In collecting the data, the researcher used observation sheet and test. The result of the research are 1) application of learning cycle model was 3.25 (good category), 2) the average score of students’ reading comprehension of analytical exposition text before and after using learning cycle model is 37 (fail category) and is 72 (good category), 3) The results of the analysis show that ttest is greater than ttable.. (7.22 > 2.08). So, the hypothesis is accepted. It means that there is any significant effect of learning cycle model in wrting narrative text for class VIII- U students’ of SMP Negeri 1 Andam Dewi. Key Word:Writing Ability, Narrative Text, Learning Cycle Model Abstrak : Tujuan penelitian ini untuk mengetahui 1) penerapan model learning cycle terhadap kemampuan menulis siswa teks narasi, 2) kemampuan menulis siswa teks narasi sebelum dan sesudah menggunakan model learning cycle, 3) apakah ada pengaruh signifikan model learning cycle terhadap kemampuan menulis siswa teks narasi. Penelitian ini menggunakan metode eksperimen dengan desain pre-experimental design dengan menggunakan one-group pretest and posttest design. Sampel penelitian ini adalah 22 siswa kelas VIII-U dengan menggunakan purposive sampling. Dalam mengumpulkan data, peneliti menggunakan lembar observasi dan tes. Hasil penelitian ini adalah 1) penerapan model learning cycle sebesar 3,25 (kategori baik), 2) nilai rata-rata pemahaman membaca siswa teks eksposisi analitik sebelum dan sesudah menggunakan model learning cycle adalah 37 (kategori gagal) dan 72 ( kategori baik), 3) Hasil analisis menunjukkan bahwa thitung lebih besar dari ttabel. (7.22 > 2,08). Jadi, hipotesis diterima. Artinya ada pengaruh yang signifikan model learning cycle terhadap kemampuan menulis teks narasi siswa kelas VIII-U SMP Negeri 1 Andam Dewi. Kata Kunci: Kemampuan Menulis,Teks Narasi, Model Learning Cycle